Дендрологічні парки Національної академії наук України: проблеми збереження історичних насаджень, пов’язані з посиленням антропогенного впливу на їхні території (на прикладі дендропарку “Олександрія” НАН України) - Galkin, S.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2011)
Results of studying of degree of pollution of territory dendrological park Olexandria by technogenic pollutants are presented. Sources of pollution are established and the maintenance of harmful substances in underground waters and a surface water of ponds dendrological park Olexandria are defined. The comparative analysis of concentration of technogenic pollutants in Olexandria and in other ancient parks is carried out.